Mapping of choriocapillaris vascular density in young and aged healthy subjects. Issue 5 (September 2022) - Bartol-Puyal, Francisco de Asís; Isanta, Carlos; Calvo, Pilar; Méndez-Martínez, Silvia; Ruiz-Moreno, Óscar; Pablo, Luis
Purpose: To compare macular vascular density (VD) of the choriocapillaris (CC) between young and aged healthy individuals. Methods: A cross-sectional study was performed enrolling young and senior healthy individuals of Caucasian race and an axial length (AL) lower than 26 mm, and without systemic or ophthalmological diseases. CC VD was imaged with DRI Triton OCTA using a 6 × 6 mm macular analysis. Internal software delimited CC boundaries and gave colour pictures, which were analysed and codified into numbers, and a grid of 30 × 30 VD values was obtained. Two-dimension (2D) and three-dimension (3D) representations were created. Results: 53 eyes of 53 young healthy individuals and 30 eyes of 30 senior healthy individuals were enrolled. Mean age was 27.17 ± 3.90 years, and 67.00 ± 7.41 years, respectively (p < 0.001). There were no differences in intraocular pressure (IOP) or AL (23.73 ± 0.79 mm, 23.18 ± 0.80 mm, respectively, p = 0.24). There were differences in foveal VD and in temporal perifoveal macula, but not in nasal perifoveal macula. Foveal VD was the highest in both groups. Conclusions: Foveal CC VD has been found to be considerably high with this method, and it is the area which most decreases with age. Nasal perifoveal VD is not reduced in older individuals. These outcomes are opposite to other studies using different methods but they are in line with previous histological findings.